Arrangements in the Field of Press in Indonesia - Mukhlish Muhammad Maududi; Asmak Ul Hosnah (Budapest International Research and Critics University, 2022)
The development of media regulation in Indonesia follows the political rhythm. The rule of Government under President Sukarno (1959-1966) and President Suharto (1966-1998) put the press under rigorous control of the Government. The Government controls the media either through legislation or through licensing mechanisms. A media-stopped publisher is writing criticism, and then the Government will revoke its publishing license. The editor of a critical media will serve life in prison after its publication is eradicated. The revocation of the media licenses never went through a judicial process. The Government strictly restricts the right to free speech and information rights for citizens. Political reforms after Suharto's Government in 1998 brought a strengthening of press freedom